2022
DOI: 10.1177/20543581221097456
|View full text |Cite
|
Sign up to set email alerts
|

Use of Google Analytics to Explore Dissemination Activities for an Online CKD Clinical Pathway: A Retrospective Study

Abstract: Background: Data on dissemination strategies that generate awareness of clinical pathways for kidney care are limited. Objective: This study reports the application of Google Analytics to describe the reach and use of the Chronic Kidney Disease Pathway (CKD-P) using a multi-faceted dissemination strategy. Design: The design of this study is a retrospective descriptive study. Setting: This study was conducted in Alberta, Canada. Patients: Individuals who accessed the CKD-P Web site between November 5, 2014, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Use of renal care pathways such as the Alberta Kidney Pathway [ 41 ] have made referral and triage processes more efficient [ 42 ]. The Alberta Kidney Pathway has shown to lead to an increase in urine ACR testing especially in non-diabetic patients [ 43 ] and prior work has examined ways to disseminate this tool locally [ 44 ]. In studies focused on electronic advice requests and consults to nephrologists where 18% [ 45 ] to 27% [ 46 ] of the consults were related to CKD, researchers found that only a minority of electronic system referrals led to in-person consults [ 45 , 46 ] highlighting the potential of e-referrals to reduce in-person nephrology visits.…”
Section: Discussionmentioning
confidence: 99%
“…Use of renal care pathways such as the Alberta Kidney Pathway [ 41 ] have made referral and triage processes more efficient [ 42 ]. The Alberta Kidney Pathway has shown to lead to an increase in urine ACR testing especially in non-diabetic patients [ 43 ] and prior work has examined ways to disseminate this tool locally [ 44 ]. In studies focused on electronic advice requests and consults to nephrologists where 18% [ 45 ] to 27% [ 46 ] of the consults were related to CKD, researchers found that only a minority of electronic system referrals led to in-person consults [ 45 , 46 ] highlighting the potential of e-referrals to reduce in-person nephrology visits.…”
Section: Discussionmentioning
confidence: 99%
“…One online CKD clinical pathway found the interaction time between the user and CKD pathway website to be only 2 min 8 s, and the end-user (provider or researcher) was not clearly defined [77], whereas another resulted in improvements in uACR testing, although primarily in patients who did not have diabetes [78]. Other clinical pathways have been used to support future patient-centered approaches [79], visualize patterns of the co-progression of multiple clinical events in a chronic disease (such as CKD) by using patients' own clinical data [80], or improve and/or maintain quality of care while reducing costs for patients with CKD (i.e., CMS ESRD treatment choice [ETC] model) [81].…”
Section: Existing Care Pathwaysmentioning
confidence: 99%
“…The numbers of users that are new to a website or revisiting a website [4,13,16] Session Count and Length A session refers to a period of time that a user is active on a website. These variables count the number of sessions and their durations [16][17][18]20,21] Bounce Rate…”
Section: New and Returning Usersmentioning
confidence: 99%
“…Bounce rate is the ratio of users that visit a website exiting without going to the second page. It usually means that users do not achieve their goals through interacting with a website [6,7,10,13,[16][17][18]20,21] Time on Site The duration of time users spent on a website [6,10,13,[16][17][18][20][21][22] Page Views The total number of web pages viewed in a session on a website [7,10,11,13,[16][17][18][20][21][22] Stem cell science is a particularly challenging space for people seeking information to navigate due to the proliferation of commercial clinics marketing unsubstantiated claims directed towards consumers about their reputed "stem cell" service; a heightened awareness of the promise of stem cell science exists, and unmet needs of many living with currently incurable conditions affecting their quality of life [26]. In addition, because of the complexity of stem cell treatments, involving different body parts, treatment choices and fast-paced research, patients and information consumers demand credible, understandable and easy-to-access information in this space [19].…”
Section: New and Returning Usersmentioning
confidence: 99%
See 1 more Smart Citation